The Regression Analysis of Factors Contribute to University Students’ Academic Performance - Farahiyah Akmal Mat Nawi; Nor Lela Ahmad; Mohd Zulkifli Abdullah; Nor Farehan Omar; Natasha Dzulkarnain; Syarifah Mastura Syed Abu Bakar; Muna Wadhiha Mohd Fauzi (Information Management and Business Review, 2023)
Malaysia Education Blueprint 2015-2025 (Higher Education) mainly highlighted sustaining the quality of higher education in this country. One of the crucial focuses is concerned with improving the graduate’s academic performance. Align with the Government’s aim UiTM has taken a progressive action to blend the current environmental scenario and higher education reform as espoused by the Minister of Education. The UiTM Strategic Plan 2025 was established to improve its performance as well as the quality of Bumiputera’s education quality. This study reports on assessing the various outer factors related to university students’ academic performance concentrating on the relationship between teaching and learning approaches, family and peer influences and student’s financial with academic performance among UiTM’s students. A theoretical framework was constructed to examine the relationship between variables. Next, a quantitative study has been carried out to gather the respondent’s feedback. An adapted survey consisting of 25 items with 5 point Likert scale was distributed to 497 respondents using the convenience sampling procedure. Data were then analyzed using the Statistical Procedure for Social Science (SPSS) to test the hypotheses. The result confirmed the hypothesis in determining the significance between the constructs. Family and peer influence was identified as the most influence factor on student academic performance (r = 0.584, p = 0.000, p < 0.05). The result also revealed that the teaching and learning approach and family and peers influence the student’s academic performance.